Facebook time: Technological and institutional affordances for media memories. (November 2014) - Kaun, Anne; Stiernstedt, Fredrik
People are spending increasingly more time on social media platforms, with Facebook being the biggest and most successful. Historically, media technologies have for long been considered of importance for the structuration and the experience of time in general. In this article, we investigate the technological affordances of Facebook for the temporal experiences of its users. Relying on a case study of a Facebook page dedicated to media memories, we link user experiences to technological and institutional affordances. By doing so, we seek to answer the question of how a business model and an infrastructure that largely build on immediacy and newness are experienced and negotiated by users that engage in a multiplicity of durations and time layers in their everyday lives. Drawing on a platform analysis, in-depth interviews and a survey among the users of the page "DT64—Das Jugendradio der DDR, " we develop the concept of "social media time" while considering notions of the archive, flow, and narrative, which contribute to shedding light on how specific media technologies afford specific temporalities. We conclude by discussing the consequences for the users and society at large.